Psychiatric Difficulties in Children with Celiac Disease and the Relationship between Adherence to Treatment and Parental Attitudes - , Didem Ayyıldız, Zeliha Demirtaş, Emine Kınacı (Turkish Journal of Gastroenterology 1, 2024)
Background/Aims: Our knowledge of the factors related to parenting styles affecting adherence to diet in children with celiac diseases (CDs) and the association between psychiatric difficulties and diet compliance is largely based on limited data. Therefore, our work aims to examine primarily coexisting psychiatric difficulties in children with CD and raising attitudes of their parents and secondarily the relationship among adherence to treatment, psychiatric difficulties, and parental attitudes.Materials and Methods: Children aged 4–12 years (n = 42) who have been followed up with the diagnosis of CD in a Paediatric Gastroenterology Outpatient Clinic were compared with those of healthy controls (n = 31). One of the parents was asked to fill out the socio-demographic information form, Diet Compliance Form (only the patient group), “Parental Attitude Research Instrument” (PARI) and Strengths and Difficulties Questionnaire—parent form (SDQ).Results: The scores from “emotional problems,” “peer relationship problems,” and “total difficulties” areas were statistically significantly higher in the disease group than healthy controls. The average score of SDQ subscales and none of the PARI subscales differed between dietary compliance +/− groups. Significant positive correlations were detected between disease duration and PARI—overprotection/extreme motherhood (r = .421, P = .017) and PARI—strict/hard discipline (r = .368, P = .038) subscales.Conclusion: Clarifying the factors related to parenting that may affect patients’ adherence to a gluten-free diet will contribute positively to the course of the disease and the quality of life of patients and their families. Cite this article as: Ayyıldız D, Demirtaş Z, Kınacı E. Psychiatric difficulties in children with celiac disease and the relationship between adherence to treatment and parental attitudes. Turk J Gastroenterol. 2024;35(9):743-749.